THE PHONOLOGICAL PROCESS OF SEMIVOWEL INSERTION IN BAHASA INDONESIA - Kartika Eva Rahmawati; Agus Subiyanto (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2021)
The phonological process shows the changing of sounds and the rules that govern the work. These sound changes can occur in vowels, consonants, and even semivowels. This study focuses on the sound changes that occur in semivowels [y] and [w], especially in Indonesian vocabularies. This study aimed to investigate the quantity of diphthong diversity in Bahasa Indonesia, as the basis for examining the role and patterns of [y] and [w] insertion, as well as when [y] and [w] cannot be inserted into some words in Bahasa Indonesia. This study also emphasizes the location where [y] and [w] are inserted by using a spectrogram. The data collection used the observation method. The list of data was taken from Kamus Besar Bahasa Indonesia (KBBI) and pronounced by an Indonesian native speaker. The spoken data are transcribed into the phonetic form using the note-taking technique. The analysis was done through the syllabic structural process based on Schane. The results present that [y] is inserted between the diphthongs ia, iu, ie, io, ea, and eo. Then, [w] is inserted between the diphthongs ua, ui, ue, uo, and oa, and the insertion of [y] and [w] does not appear when they meet with the diphthongs ai, au, ae, ao, ei, eu, oi, ou oe. The spectrograms in this study are used to see and present the insertion of [y] and [w].